2016
DOI: 10.1182/blood-2016-05-711424
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic profiling of mouse primary HSPCs reveals new regulators of HSPC mobilization

Abstract: Key Points Combining flow cytometry and high-performance mass spectrometry enables phosphoproteomic analysis of rare blood cell populations. ARHGAP25 dephosphorylation augments activity and promotes blood stem and progenitor cell mobilization by enhancing CXCL12 and Rac signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 65 publications
2
31
0
Order By: Relevance
“…Applying a newly developed quantitative phosphoproteomic analysis, Leo Wang and his colleagues identified ARHGAP25 as a protein that showed highly different phosphorylation profiles in resting and mobilized hematopoietic stem and progenitor cells (HSPC). 27 They could also show that ARHGAP25 activity was essential for mobilization of hematopoietic cells from the bone marrow. Our group revealed that…”
Section: Smg-dependent Biological Processes?mentioning
confidence: 99%
“…Applying a newly developed quantitative phosphoproteomic analysis, Leo Wang and his colleagues identified ARHGAP25 as a protein that showed highly different phosphorylation profiles in resting and mobilized hematopoietic stem and progenitor cells (HSPC). 27 They could also show that ARHGAP25 activity was essential for mobilization of hematopoietic cells from the bone marrow. Our group revealed that…”
Section: Smg-dependent Biological Processes?mentioning
confidence: 99%
“…Our findings strongly suggest that the leukocytespecific RacGAP ARHGAP25 is a critical player in TNF-a-induced, Rac-mediated actin reorganization in neutrophils. Two recent reports provide important information on its physiological role: ARHGAP25 was shown to be required for actin depolymerization in the course of phagocytosis (21,44), and it was demonstrated to undergo significant changes in its phosphorylation pattern and GAP activity upon biological stimulation (45). TNF-a-initiated modulation of the phosphorylation pattern of ARHGAP25 with subsequent alterations of its GAP function may provide the link between the cytokine effect and the actin cytoskeleton rearrangement.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inhibition of ARHGAP25 activity leads to augmented CXCL12 signaling. 84 In vivo, CXCL12 is truncated by the membranebound extracellular peptidase CD26 (dipeptidyl peptidase-4, DPP4), which is expressed on the surface of many cell types in the BM, including ECs and a subset of HPCs. 85,86 This peptidase is essential for G-CSF-induced HSPC mobilization, as Dpp4 −/mice show significantly decreased G-CSF-induced HSPC mobilization compared with wild-type mice.…”
Section: Integrins and The Cxcl12/cxcr4 Axis In Mobilizationmentioning
confidence: 99%